Party discipline and government spending: theory and evidence - Curto-Grau, Marta; Zudenkova, Galina (Discussion paper series, 2016)
This paper studies the relationship between party discipline and discretionary spending with theory and data. We propose a theoretical model in which a politician faces a conflict between her constituents' interests and the party line. Party loyalty is electorally costly for the politician and is therefore rewarded by the party leader with greater amounts of discretionary spending allocated to the politician's constituency. The more intense the conflict between the voters' and the party's interests, the more grants the district receives. Using panel data on party discipline in the U.S. House of Representatives and federal grants to congressional districts between 1984 and 2010, we provide evidence that districts represented by loyal legislators receive greater amounts of discretionary spending. This effect holds only for legislators in the majority party, who may enjoy a legislative advantage. Districts represented by loyal legislators who face a greater conflict of interest between following the party and serving their constituents (e.g., Republican legislators representing liberal-leaning districts) are rewarded to a larger extent.
Keywords: Arbeitspapier; Graue Literatur